Effect of Wildfire on Soil-Water Characteristics of Natural Slope Containing Temperature Sensitive Silica-alumina Polymorph Minerals - Mohd Yuhyi, Mohd Tadza; Anis Ayesha, Noraini (AENSI Publishing, 2016)
Wildfires increased hillslopes erosion and surface runoff. The effect increased by several magnitudes when subjected to high intensity of precipitation during prolonged rainy seasons. The changes in geotechnical properties of soils affected by wildfire may jeopardize the stability of the slopes. In this study, soil specimens containing thermal sensitive nesosilicate polymorphs undergone wildfire and non-exposed to fire were collected and tested in order to understand the changes to the geotechnical properties and water retention behavior. Similarly, the changes to the slope were monitored up to a period of 270 days. The suction-water content soil water characteristic curves (SWCCs) were established for the soils using a chilled mirror dew-point hygrometer. In addition, the changes in the mineral compositions were also evaluated using X-ray diffraction analysis. Test results indicated that, the plasticity characteristics of the soils decreased after being burned. Concurrent to the decreased in the plasticity, the suction-water content established for soil exposed to wildfire was found to be slightly lower than that of unburned soils for suction lower than 1.5 MPa. Nesosilicates was found to be completely altered and affected by fire, whereas quartz minerals were found to be unaffected. Erosion occurred on-site was found to be attributed to reduction in the plasticity characteristics and changes to the overall mineral structure of the soil. Furthermore, the removal of vegetation as affected by fire reduced the slope surface cover and caused erosion of the slope to occur.